Keefektifan Metode Pembelajaran Berbasis Masalah Terhadap Hasil Belajar Pada Materi Matematika Ekonomi: Fungsi Permintaan Dan Penawaran Pada Siswa SMK - Bayu Suwandra (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The purpose of this study is to determine whether the problem-based learning method is effective when used in the classroom, as seen from students’ learning outcomes. This study consists of an experimental class that uses the problem-based learning method and a control class that uses a conventional method. The data analysis techniques used in this study are the t-test and the N-gain test. The results of the study conclude that the problem-based learning method has a significant effect on students’ learning outcomes in the topic of demand and supply functions, as indicated by the t-test result showing 0.31 > 0.05. It is also effective for classroom use based on the N-gain test result with a value of 78. The problem-based learning method can improve learning outcomes in economic mathematics, specifically on demand and supply functions, among students.